2016
DOI: 10.1021/acs.est.6b00071
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal and N2O Accumulation during Hydrogenotrophic Denitrification: Influence of Environmental Factors and Microbial Community Characteristics

Abstract: Hydrogenotrophic denitrification is regarded as an efficient alternative technology of removing nitrogen from nitrate-polluted water that has insufficient organics material. However, the biochemical process underlying this method has not been completely characterized, particularly with regard to the generation and reduction of nitrous oxide (NO). In this study, the effects of key environmental factors on hydrogenotrophic denitrification and NO accumulation were investigated in a series of batch tests. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 49 publications
(127 reference statements)
0
43
1
Order By: Relevance
“…Experimental data from Li et al () on N 2 O emission during hydrogenotrophic denitrification were used to calibrate and validate the model. Li et al () used a hydrogen gas‐ and nitrate‐fed denitrifying culture, acclimated and cultivated for 54 months continuously in three parallel 2‐L lab‐scale continuous‐flow reactors at pH 7.0 ± 0.5 at 30 ± 1 °C, with a cycle time of 12 hr, to study the N 2 O accumulation during hydrogenotrophic denitrification.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental data from Li et al () on N 2 O emission during hydrogenotrophic denitrification were used to calibrate and validate the model. Li et al () used a hydrogen gas‐ and nitrate‐fed denitrifying culture, acclimated and cultivated for 54 months continuously in three parallel 2‐L lab‐scale continuous‐flow reactors at pH 7.0 ± 0.5 at 30 ± 1 °C, with a cycle time of 12 hr, to study the N 2 O accumulation during hydrogenotrophic denitrification.…”
Section: Methodsmentioning
confidence: 99%
“…N 2 O, a highly undesirable significant intermediate, can thus accumulate and subsequently emit to the atmosphere during hydrogenotrophic denitrification, which has raised increasing concerns due to its potent greenhouse gas effect and ozone depleting ability (Liu et al, , ; Ravishankara, Daniel, & Portmann, ). It has been reported that the amount of N 2 O accumulation in hydrogenotrophic denitrification system ranged from 0.05% to 15.2% of the influent nitrogen load (Li et al, ). Therefore, understanding N 2 O accumulation in hydrogenotrophic denitrification is of great importance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations